Struktur Komunitas Mangrove Di Lapangan Senoro, Kabupaten Banggai, Sulawesi Tengah - Tis'in, Musayyadah; Mansyur, Kasim; Safir, Muhammad; Artha, Shanti Nata; Nurdin, Enrico Putra; Maulidiansa, Clara (Universitas Madako Tolitoli, 2025)
Mangrove ecosystems provide a variety of ecosystem services, making mangroves an important/vital ecosystem in coastal areas. Mangrove ecosystems provide abundant fishery resources, supporting food security and improving the economy of the community. This study aims to examine the structure of mangrove communities in the waters of Lapangan Senoro, which is a Mining Concession Area (MCA) operated by JOB Pertamina-Medco E&P Tomori Sulawesi (JOB Tomori). Mangrove data collection was conducted using 10 m x 10 m transects at two stations representing natural mangrove communities and rehabilitated mangroves. The results of the study indicate that there are 10 mangrove species at the study site, dominated by Rhizopora apiculata. The diversity of mangroves at the study site, both those representing natural mangrove communities and those resulting from rehabilitation, falls into the “moderate” category, meaning that the mangrove communities have a fairly balanced level of complexity. Based on the INP value, the R. apiculata species plays the most important role in the ecosystem. The density of mangroves at Senoro Field is categorized as good/very dense.